2017
DOI: 10.4103/jcd.jcd_200_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the amount of debris extruded apically using conventional syringe, passive ultrasonic irrigation and EndoIrrigator Plus system: An in vitro study

Abstract: Aim:The aim of this study is to compare the effects of conventional syringe, passive ultrasonic irrigation (PUI), and EndoIrrigator Plus on the amount of apically extruded debris.Materials and Methods:Thirty extracted human mandibular premolars were selected and randomly assigned to three groups (n = 10). The root canals were irrigated with conventional syringe, PUI, and EndoIrrigator Plus. Sodium hypochlorite was used as an irrigant, and debris was collected in a previously described experimental model (Myers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
0
13
1
5
Order By: Relevance
“…In addition, in the present study, there was no difference in the amount of apical debris extrusion using the PIPS, PUI and MI methods. Others reported that PUI produced less debris extrusion than MI (17,22,27). In the present study, PUI caused (by weight) less apical debris extrusion than MI, but there was no statistically significant difference between the amount of debris extrusion using MI and PUI.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, in the present study, there was no difference in the amount of apical debris extrusion using the PIPS, PUI and MI methods. Others reported that PUI produced less debris extrusion than MI (17,22,27). In the present study, PUI caused (by weight) less apical debris extrusion than MI, but there was no statistically significant difference between the amount of debris extrusion using MI and PUI.…”
Section: Discussioncontrasting
confidence: 55%
“…also concluded that ultrasonic irrigation extruded lesser debris in comparison with conventional syringe irrigation. [18] Open-ended needles generate positive pressures in excess of central venous pressure, as stated by Khan et al . [19] A study by Boutsioukis et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the cases where vapor lock presence was demonstrated, the MDA [20] method was performed with a dedicated F3 gutta-percha cone, using back and forth movements inside the canal for 10 s. In the evaluation of PUI efficacy performed on the endo training block similar to the close-ended systems whose terminal portion was closed using orthodontic wax, a watery solution was delivered inside the endo training blocks using a disposable syringe, with a tip-opened 25 G diameter needle, located 5 mm beyond the entrance of the resin block; this technique is commonly known as PPI [31]. In the cases where vapor lock presence was demonstrated, the PUI method was performed using a Woodpecker ultrasonic tip (28/32 kHz) (Guilin Woodpecker Medical Instrument, Guilin, Guangxi, China) [32], with a 0.8 mm ø mounted on a Satelec handle(Satelec, Bordeaux, France), acting inside the block for 10 s.…”
Section: Methodsmentioning
confidence: 99%
“…In the evaluation of PUI efficacy performed on the endo training block similar to the close-ended systems whose terminal portion was closed using orthodontic wax, a watery solution was delivered inside the endo training blocks using a disposable syringe, with a tip-opened 25 G diameter needle, located 5 mm beyond the entrance of the resin block; this technique is commonly known as PPI [31]. In the cases where vapor lock presence was demonstrated, the PUI method was performed using a Woodpecker ultrasonic tip (28/32 kHz) (Guilin Woodpecker Medical Instrument, Guilin, Guangxi, China) [32], with a 0.8 mm ø mounted on a Satelec handle(Satelec, Bordeaux, France), acting inside the block for 10 seconds. The photos were recorded with a digital camera (Canon 1100D, Tokyo, Japan) at a fixed position and magnification using stable supports for the digital camera and specimens.…”
Section: Methodsmentioning
confidence: 99%